Paradigm Change of Local Tax - Ismail, Tjip (UI Scholars Hub, 2012)
Together with the implementation of local autonomy, Indonesia implemented the concept of fiscal decentralization, manifested through the local government’s authority to collect tax and retribution. The implementation process of such policy, however, still triggers certain problems, such as people’s perception of tax as burdensome obligation without any right of counter-achievement (compensation) for its payment. This research aims to study the paradigm change of local tax, viewed from three aspects: (1) the paradigm shift of local tax in Indonesian governance system, (2) new paradigm of local tax, (3) the effect of local tax paradigm change toward local developments. The approach used is qualitative with data collection techniques of observation, in-depth interview and literature study. The result shows that the paradigm change of local tax is necessary since there is a spectrum of democracy development in society due to the fact that the revenue from local retribution is less than the revenue from local tax. As a consequence, local tax paradigm should be altered i.e. local tax must give counter-achievement for the related tax sectors. Hence, local tax paradigm change shall increasingly influence the taxpayers to obediently fulfill their obligation of paying local tax since they may directly enjoy the benefit of their tax.